2017
DOI: 10.9734/ajrb/2017/v1i1329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Mineral and Phytochemical Analysis of Soil and Lactuca sativa Grown in the Vicinity of Cement Company of Northern Nigeria (Sokoto Cement) and Usmanu Danfodiyo University Sokoto (Kwalkwalawa)

Abstract: Environmental pollution is a major issue which confronts industry and business in today’s world on daily basis. Industrial activities are the leading cause of metals emission, often associated with soil and plant metal concentration in adjacent regions. Cement industry is one of the 17 most polluting industries listed by the central pollution control board (CPCB). Impact of dust deposition from Cement Company of Northern Nigeria on the proximate and phytochemical concentrations of lettuce (Lactuca sativa) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Studies by Inuwa et al [40] showed that the levels of some heavy metals within the study region reached 0.1µg/g Cd, 83.4 µg/g Cr, 486.0µg/g Pb and 22.9µg/g Ni. Dalhat et al [57] also reported higher Pb, Zn, Cr and Cu concentrations in soil and Lactuca sativa grown in the area as against distant compared references. These findings are further supported by the work of Ibrahim et al [45] who observed that the finished product of the industry (cement) contains appreciable amount of heavy metal that can reach up to 6.67 ppm Mn, 7.93 ppm Ni, 2.64 ppm Cr and 2.52 ppm Cd making it highest in Ni and Cr among the tested pairs.…”
Section: Resultsmentioning
confidence: 85%
“…Studies by Inuwa et al [40] showed that the levels of some heavy metals within the study region reached 0.1µg/g Cd, 83.4 µg/g Cr, 486.0µg/g Pb and 22.9µg/g Ni. Dalhat et al [57] also reported higher Pb, Zn, Cr and Cu concentrations in soil and Lactuca sativa grown in the area as against distant compared references. These findings are further supported by the work of Ibrahim et al [45] who observed that the finished product of the industry (cement) contains appreciable amount of heavy metal that can reach up to 6.67 ppm Mn, 7.93 ppm Ni, 2.64 ppm Cr and 2.52 ppm Cd making it highest in Ni and Cr among the tested pairs.…”
Section: Resultsmentioning
confidence: 85%
“…The Allium sativum spice showed higher ash contents (1.44%) compared to the Allium cepa spice. The Ash content refers to the inorganic residues remaining after either ignition or complete oxidation of organic matter in the sample and gives an overview of the mineral content of the material [13]. High ash content implies high mineral contents in the spices, Allium sativum is likely to be a better source of minerals in the diet as compared to the Allium cepa (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A 10ml of Fehling's solution was added and the mixture was boiled. A brick red precipitate was observed, which indicate the presence of glycosides [12,13].…”
Section: Test For Glycosidesmentioning
confidence: 99%
See 1 more Smart Citation